Gestión Presupuestaria En El Gobierno Autónomo Descentralizado Parroquial Isla De Bejucal - Herrera Tamayo, Estalin Vicente (2018)
The Parish of Bejucal Island, founded on April 23, 1884, is one of the oldest parishes in the Province of Los Ríos, with an approximate population of 9,000 inhabitants, which borders the San Juan and Guare parishes to the north, to the south with the parishes Baba and Pimocha to the east with San Juan and Pimocha and to the West with Baba and Guare. For this parish the construction of the Vinces-La Isla San Juan road meant a very important change for the economic development of this parish, the same one that is based on the agricultural production especially of the banana production, since before the transportation route for This parish was through boats to people as well as agricultural products and anyone who needs this means of transport. The autonomous decentralized parish government of Isla de Bejucal administered by its President Miguel Botto Carrasco at present, this entity since its creation has been carrying out procedures and works for the benefit of its citizens, and ensuring the proper territorial ordering of the parish and thus also with the equipment, infrastructure and viability of it etc.